Komunikasi dan Kolaborasi: Pemerintah, Lembaga Non Pemerintah, dan Masyarakat dalam Pengelolaan Sampah Plastik - Ade, Risan Agung; Andriansyah (Kinesik, 2024)
This research aims to determine environmental collaboration between the government, Non-Governmental Organizations (NGOs), and the community in reducing plastic waste in Makassar City. The research method used is a descriptive qualitative approach. Data was obtained through interviews, observation and documentation. The research results show that collaboration between the Makassar City Environmental Service (DLH), the Peduli Negeri Foundation (YPN), and the community has shown success in reducing plastic waste. Through educational campaigns, waste bank programs and supportive government policies, this collaboration has succeeded in increasing public awareness and participation in efforts to reduce plastic waste. Good coordination and synchronization between government, NGOs and the community is the key to the success of this collaboration. The government provides regulations, policies and infrastructure, while YPN focuses on education and outreach, and the community plays an active role in sorting waste and participating in recycling programs.